Intensified biodiesel production from waste cooking oil and flow pattern evolution in small-scale reactors - Tsaoulidis, Dimitrios; Garciadiego-Ortega, Eduardo; Angeli, Panagiota (Frontiers in Chemical Engineering, 2023)
In this paper, the transesterification reaction of waste cooking oil (WCO) with methanol using KOH as catalyst to produce biodiesel was performed in a micro-reactor (1 mm ID) using a cross-flow inlet configuration. The effects of different variables such as, methanol-to-oil molar ratio, temperature, catalyst concentration, and residence time on biodiesel yield, as well as the associated flow patterns during the transesterification reaction were investigated and the relationship between flow characteristics and mass transfer performance of the system was examined. The work reveals important aspects for the characterisation of intensified reactors in terms of hydrodynamic behaviour and mass transfer performance. It was found that high yield (>90%) of biodiesel can be achieved in one-stage reaction using cross-flow micro-reactors for a wide range of conditions, i.e., methanol-to-oil molar ratio: 8-14, catalyst concentration: 1.4-1.8% w/w, temperature: 55-60 ºC, and residence times: 55-75 s.